Determination of the exercise intensity corresponding with maximal lactate steady state in high-level basketball players - Dragonea, P.; Zacharakis, E.; Kounalakis, S.; Kostopoulos, N.; Bolatoglou, T.; Apostolidis, N. (Research in Sports Medicine, 2019)
The purpose of the present study was to define the maximal lactate steady state (MLSSmeas) in high-level male basketball players and to compare it with the lactate turnpoint (LTP) and the respective point derived form a prediction method (MLSScal). Twelve high-level basketball players underwent one maximal and several submaximal tests on a treadmill on different days where MLSS and LTP were measured. MLSSmeas was observed at 75% of the maximal treadmill speed, at 77% of VO2max, at 88% of HRmax and at [La-] of 3.7 mmol.l-1. No differences were observed between MLSSmeas and LTP in any of the measured variables. A good agreement was observed between MLSSmeas and LTP, as well as between MLSSmeas and MLSScal. Therefore, LTP and MLSScal are offered as acceptable approaches to predict MLSS, but not all the indices used to define MLSS presents high agreement between the methods used.